OWNERSHIP RIGHTS TRANSFER OF OFFICIAL RESIDENCE LAND - Bintang Ulya Kharisma (Universitas Muhammadiyah Ponorogo, 2020)
In a legal state, land has a very important role in human life. It can determine the existence and the sustainability of legal actions. In its development, the government or private sector companies provide Official Residences to their employees, or what may be called a state house. Based on the law, the Official Residence is a building owned by the state, and functions as a residence or a dwelling. It serves as a developmental facility for families and supports the job implementation of officials and/or government employees. The humans’ need for land as a place of dwelling may cause conflicts regarding the provision of the Official Residence. The method used in this research is the juridical-normative method. It uses secondary data. The ownership rights transfer of the Official Residence to private sectors may happen without violation of the constitution, as it is regulated in the Presidential Decree No. 11 of 2008 which states that the tenant may own the Official Residence with some conditions. For example, the house must be an Official Residence Group III. The rightful tenant must file a request to its related Department. Then, the tenant and the related department create a Lease Agreement. After the tenant settles the debt, he/she may own the house.